Atavistic Stomatal Responses to Blue Light in Marsileaceae. Issue 3 (25th August 2020) - Westbrook, Anna S.; McAdam, Scott A.M.
Abstract : Marsileaceae species exhibit unique stomatal responses to blue light, unlike all other leptosporangiate ferns previously studied. Abstract: Stomata respond to changes in light environment through multiple mechanisms that jointly regulate the tradeoff between carbon assimilation and water loss. The stomatal response to blue light is highly sensitive, rapid, and not driven by photosynthesis. It is present in most vascular plant groups but is believed to have been lost in the ancestor of leptosporangiate ferns. Schizaeales and Salviniales are the only leptosporangiate orders that have not been tested for stomatal responses to a low fluence of blue light. We report that these stomatal responses are absent in Lygodium japonicum (Schizaeales). In contrast, we observed stomatal responses to a low fluence of blue light in Regnellidium diphyllum and Marsilea minuta (Marsileaceae, Salviniales). In R. diphyllum, blue light triggered stomatal oscillations. The oscillations were more sensitive to atmospheric carbon dioxide concentration than to humidity, suggesting that the blue light responses of Marsileaceae stomata differ from those of angiosperms. Our findings suggest that Marsileaceae have physiologically diverged from other leptosporangiate ferns, achieving unusually high photosynthetic capacities through amphibious lifestyles and numerous anatomical convergences with angiosperms. Blue light stomatal responses may have contributed to this divergence by enabling high rates of leaf gas exchange in Marsileaceae.